The Positive Halochromism of Phenolate Dyes in Hydroxylic Solutions of Tetraalkylammonium Cations - Caroli-Rezende, M; Aracena-Astudillo, A; Aracena-Astudillo, A; Dominguez-Caru, M (2012)
By contrast with the negative halochromic behaviour shown by phenolate betaines in the presence of alkaline and alkaline-earth cations, the addition of tetraalkylammonium salts to hydroxylic solutions of these dyes generate bathochromic shifts of their charge-transfer band. This positive halochromic behaviour by organic cations was examined systematically and its origin rationalized by nonspecific changes of the medium permittivity, and by specific dye-cation interactions in solution. © 2011 Elsevier B.V.